THE EFFECT OF SUPERVISION , WORK CULTURE , AND TRUST TO PERFORMANCE OF ELEMENTARY PUBLIC-SCHOOL PRINCIPAL OF WEST JAKARTA CITY - Akbar, Muhammad Fahmi; Akbar, Ma’ruf; Mukhtar, Mukhneri (Journal of Education Research in Administration and Management (JERAM), 2018)
The purpose of this research to determine the effect of supervision, work culture, trust, and attitudes to the performance of public elementary-school principal of West Jakarta city. To describe how much influence the effect of supervision, the culture, and trust to performance of elementary public principals of West Jakarta city. The research method used is the survey method with causal techniques. Whereas to analyze the existing or influence between one variable with another using variable path analysis. The population of West Jakarta city, and sampling procedure using the technique of sample random sampling as much as 80 principals were taken randomly. Results of the study found that the supervision of variable turned out to have effects directly to the performance; work culture also has effects directly to the performance, and trust has effects directly to the performance. Whereas trust variables prove to have direct influence from supervision and work culture. Based on the findings above, it can be concluded that the variations that occur on performance variables are supervision, work culture, and trust variables.